(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2009)
Fatimah's Kampung by Iain Buchanan is above all a very personal book. It is a book written by a meticulous person who has an eye for beauty and a heart for a deeply moral message. Fatimah's Kampung can also be read as a summary of the experience of its author who has seen more than just the old ways of his native England. As he writes in the Introduction, he recalled memories from his childhood in Southern Africa when he first came to post-independence Malaysia to teach geography for five years. He felt therefore strangely at home when he first smelled the Malaysian scents of roasted peanuts and bruised oil palm kernels, of frangipani and the forest after the rain.